2000
DOI: 10.1590/s0103-84782000000200025
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de anticorpos neutralizantes contra o herpesvírus bovino tipo 1, decorrente de infecção natural, em rebanhos com distúrbios reprodutivos

Abstract: A detecção de anticorpos anti-Herpesvírus Bovino tipo 1 (BHV-1) foi realizada, através da técnica de soroneutralização, em 1235 amostras de soro de bovinos adultos, não-vacinados contra Rinotraqueíte Infecciosa Bovina. As amostras de soro analisadas foram colhidas em 81 rebanhos, com histórico de problemas reprodutivos, incluindo animais com aptidão para carne e leite, provenientes de 30 municípios do Estado do Paraná. Na amostragem proveniente de rebanhos leiteiros, 41,9% (409/977) das amostras de soro e 90,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1
19

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 6 publications
(5 reference statements)
1
3
1
19
Order By: Relevance
“…These authors used as a cutoff point the inhibition of cell lysis at 1:4 dilutions in virus neutralization. The results obtained by Médici et al (2000) were higher than those presented in this study; however, the cutoff may have caused this disagreement. Sousa et al (2009) studied the dairy region of the island of São Luís, MA, and found that 67.5% of samples of non-vaccinated dairy cows had antibodies against BHV-1.…”
Section: Resultscontrasting
confidence: 88%
“…These authors used as a cutoff point the inhibition of cell lysis at 1:4 dilutions in virus neutralization. The results obtained by Médici et al (2000) were higher than those presented in this study; however, the cutoff may have caused this disagreement. Sousa et al (2009) studied the dairy region of the island of São Luís, MA, and found that 67.5% of samples of non-vaccinated dairy cows had antibodies against BHV-1.…”
Section: Resultscontrasting
confidence: 88%
“…Além dos fatores mencionados acima, foi demonstrado que as diferenças em prevalência podem também estar relacionadas com as cepas de vírus utilizadas para os testes laboratoriais, o que pode levar a alterações na sensibilidade da SN. No Brasil, a quase totalidade dos inqué-ritos sorológicos previamente realizados utilizaram uma das cepas de "referência" de BoHV-1 como vírus de desafio no teste sorológico (Galvão et al 1963, Wizigmann et al 1972, Mueller et al 1981, Ravazzolo et al 1989, Lovato et al 1995, Vidor et al 1995, Melo et al 1997, Cerqueira et al 2000, Médici et al 2000, Rocha et al 2001, Quincozes 2005, Dias 2006, Dias et al 2008. No presente estudo foi demonstrado que, para que seja obtida uma maior sensibilidade, os testes de SN devem ser executados frente a várias amostras de vírus.…”
Section: Resultsunclassified
“…De fato, até o presente, todos os estudos de soroprevalência de herpesvírus bovinos realizados no País foram executados somente frente a cepas de BoHV-1, não buscando animais soropositivos para o BoHV-5 (Ravazzolo et al1989, Lovato et al 1995, Vidor et al 1995, Lage et al 1996, Melo et al 1997, Cerqueira et al 2000, Médici et al 2000, Vieira et al 2003, Poletto et al 2004, Barbosa et al 2005. Além disso, os estudos prévios foram realizados frente a somente uma determinada cepa de vírus, normalmente uma amostra "referência" de BoHV-1.…”
Section: Introductionunclassified
“…VN for BoHV-1 (Los Angeles strain) was performed by using serial 2-fold dilutions of sera made in minimum essential medium as described (MÉDICI et al, 2000); sera were tested for virus neutralizing antibodies through the 1:1,024 dilutions. VN for BVDV-1 (Singer strain) was done as described (DIAS et al, 2010), using 2-fold dilutions starting at 1:5 through 1:160.…”
Section: Virus Neutralization For Bohv-1 and Bvdvmentioning
confidence: 99%